A study on key elements influencing economic growth in Malaysia: Malaysia oil price, inflation rate, stock price, exchange rate, trade openness and foreign direct investment / Alia Syafiqah Tarmuji and Rasyika Rasman - Tarmuji, Alia Syafiqah; Rasman, Rasyika (Faculty of Business Management, 2016)
This study presents evidences that Malaysia Oil Price per Ton, Inflation Rate represented by Consumer Price Index (CPI), Stock Price represented by FTSE Bursa Malaysia KLCI (FTSE KLCI), Exchange Rate per Malaysia Ringgit against US Dollar, Trade Openness represented by Export Volume and Foreign Direct Investment represented by FDI Inward are among the indicators of Malaysia’s economic growth. Factors that explain the economic growth are carefully analyzed. The study period ranges from 2005 to 2015 are used to assess the effects of Malaysia Oil Price per Ton, Inflation Rate represented by Consumer Price Index (CPI), Stock Price represented by FTSE Bursa Malaysia KLCI (FTSE KLCI), Exchange Rate per Malaysia Ringgit against US Dollar, Trade Openness represented by Export Volume and Foreign Direct Investment represented by FDI Inward. This study used Single Linear Regression and Multiple Linear Regression in order to find the inter-relationship among these variables. Based on the tests that have been carried out, Inflation Rate represented by Consumer Price Index (CPI) and Stock Price represented by FTSE Bursa Malaysia KLCI (FTSE KLCI) is said to have linkage between them. However, Malaysia Oil Price per Ton, Exchange Rate per Malaysia Ringgit against US Dollar, Trade Openness represented by Export Volume and Foreign Direct Investment represented by FDI Inward did not have any relationship towards the economic growth in Malaysia and this has been proven statistically from the test carried out in this study such as Unit Root Test, Descriptive Statistics, Preliminary Analysis and Diagnostic Test.